The interplay of nitrogen sources and viral communities in the biodegradation of atrazine in agricultural soils - Wang, Yongfeng; Radosevich, Mark; Yang, Lu; Zhang, Ying; Xie, Ninghui; Liang, Xiaolong (Frontiers in Microbiology, 2025)
Atrazine is a widely used herbicide, and its degradation is primarily mediated by microbial activity. However, the interplay between nutrient availability and viral infections on microbial degradation of atrazine remains unexplored. Here, we investigated atrazine degradation under different nitrogen amendments (ammonium, nitrate, and urine) and the influence of soil viruses (intracellular and extracellular viruses). The results showed that atrazine degradation was greater with the addition of extracellular viruses without exogenous nitrogen sources. The added nitrogen sources (nitrate and urine) completely inhibited atrazine degradation. Ammonium impeded atrazine degradation, which was promoted with the addition of intracellular viruses. The metagenomic-based evidence revealed that nitrogen amendments significantly alter bacterial and viral community composition. Peduoviridae emerged as the predominant viral family, with its prevalence and temperate phage ratio strongly influenced by nitrogen availability, underscoring the role of nutrient dynamics in shaping virus-host interactions. The presence of viruses selectively enriched atrazine degradation genes and auxiliary metabolic genes (AMGs) associated with key microbial metabolic pathways, revealing potential mechanisms by which viral infections contribute to pollutant biodegradation. The findings highlight the complex interplay between viral predation, microbial adaptation, and nitrogen-driven shifts in microbial community structure and function, offering new perspectives on how viruses shape bioremediation processes in agroecosystems.